Brugada phenocopy in diabetic ketoacidosis, the importance of the diagnostic approach. (June 2020) - Dendramis, Gregory; Sgarito, Giuseppe; Comparato, Calogero; Corrao, Salvatore; Baranchuk, Adrian
Abstract: Brugada phenocopies (BrP) are clinical entities that present with identical ECG patterns to those of true Brugada Syndrome (BrS) but are elicited by various other clinical circumstances. Our manuscript shows an interesting case of a type-1 Class A BrP in a young patient with diabetic ketoacidosis and hyperkalemia. Highlights: BrP are clinical entities that present with identical ECG patterns to those of true BrS but are elicited by various other clinical circumstances. A systematic approach to differentiate between BrP and BrS is crucial to avoid diagnostic errors that involves excessive expenses, time and referring patients to unnecessary diagnostic tests or treatments.